THE IMPACT OF BIG DATA ON SOCIETY: A TECHNICAL ANALYSIS OF BENEFITS, RISKS, AND ETHICS - Ankur Partap Kotwal , (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2024)
In the era of digital transformation, big data has emerged as a revolutionary force reshaping modern society and technological landscapes. This comprehensive article examines the multifaceted impact of big data technologies, focusing on their technical implementation frameworks, infrastructure requirements, security challenges, and ethical considerations. The article explores advanced analytics capabilities, privacy-preserving technologies, and bias detection mechanisms while providing detailed case studies of significant implementations. Through an article of current architectural approaches and governance frameworks, this analysis offers practical recommendations for organizations implementing big data solutions while emphasizing the critical balance between technological advancement and responsible data stewardship.